Evaluation of the usefulness of selected scales and methods used in the assessment of balance and physical fitness in seniors – a pilot study - Ćwirlej-Sozańska, Agnieszka; Wilmowska-Pietruszyńska, Anna; Guzik, Agnieszka; Wiśniowska, Agnieszka; Drużbicki, Mariusz (European Journal of Clinical and Experimental Medicine, 2026)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim: The risk of falls increases significantly with age. The aim of the study was to analyze the usefulness of selected scales and methods used in assessing the balance and physical fitness in seniors. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods: The study included a pilot group of 25 people aged 60-77 years of age. Fullerton Functional Fitness Test also called the Senior Fitness Test was used to assess the functional capacity. The following clinical tests were used to assess balance in seniors: “Up&Go Test”, Functional Reach Test, Tandem Stance Test, Tandem Tandem Walk, Tandem Pivot 180° and measurements on Cosmogamma stabilometric platform. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: The studies demonstrated the relationship between the results of clinical tests and the measurement of functional capacity, i.e. the relationship between the results of clinical tests and the results of measurement of path length of centre of pressure on stabilometric platform in standing on one leg with eyes open. Although there are reports in the literature concerning the research on evaluation of usefulness of the control system used to assess balance in seniors, there are no uniform procedures indicating which tests and quantitative methods for assessing the balance should be analyzed to ensure the credibility of the research. It was demonstrated that the results of one of the tests concerned in this paper can be a fairly reliable prediction of the results for another one. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: The tests: “Up & Go”, Tandem Walk, Tandem Pivot 180° and Functional Reach, which were used in this study, are valuable tools for qualitative assessment of the balance in the population of people over 60 years of age. Stabilometric assessment of the balance in seniors correlates with the results of clinical tests. Further studies are necessary involving a larger group of people in order to confirm the reliability of the results.